The student government as an educational method. Rich past and poor present - Kiszka, Monika (Kultura-Społeczeństwo-Edukacja, 2022)
Democratic and governmental transformations require students to develop numerous civic skills that will allow them to fully participate in adult life and enjoy all civil rights. They constitute a very important link in the school education cycle, but above all, in civic education. The student government creates one of the most important forms of social activity available to students, which allows them to develop, among others, organizational skills. It also furthers the child’s development. Active participation in the student government is an indicator of students’ self-awareness and development; it directs their activities towards cooperation and readiness to carry out tasks for the benefit of the school community. However, despite numerous educational aspects, creating optimal conditions for the functioning of the student government is the most difficult task of a modern school (Sowisło, 1996, p. 7).